Repensando o negro no debate da formação social brasileira: a contribuição de Joel Rufino dos Santos - Martins, Jonas Lara (Universidade Federal de São Carlos, 2022)
The work of Joel Rufino dos Santos contains an important reflection on the contemporary world, emphasizing a new version of Brazilian history in the midst of the consolidation of industrial society in Brazil, a moment when intellectuals debated the theme of the national project and acted in full process of implementation and routinization of the social sciences in Brazil, privileging different themes and problems along this trajectory. The schedule of issues analyzed by Rufino is anchored in the trajectory of racial exclusion long rooted in the Brazilian tradition, under multiple aspects. Although Joel Rufino do Santos' work is extensive and deals with a complex thematic schedule, this work intends to analyze the author's intellectual thinking on two points: the first, closer in nature to the debate on social thought and interpretations about Brazil, will focus on a critique and review of the history of Brazilian education and the role of black people in it; the second will deal with the trajectory of Joel Rufino dos Santos. In the end, it is intended to give visibility to the thought of this black intellectual in whose agenda of reflection important themes are found for the understanding of how the racial question, the theme of subjectivity, and the sociopolitical dimension of blacks are articulated with national formation (yesterday and today).
Rethinking the black in the debate on Brazilian social formation: the contribution of Joel Rufino dos Santos
Keywords: Joel Rufino dos Santos; Relações raciais; Pensamento social brasileiro; Negro; Brazilian social theory; Black; Race relations; CIENCIAS HUMANAS::CIENCIA POLITICA; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL; OUTROS::CIENCIAS SOCIAIS; CIENCIAS HUMANAS::SOCIOLOGIA::FUNDAMENTOS DA SOCIOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA DO CONHECIMENTO